A Comparison of EFL Teachers Use of ICT as Learning Media Seen from Gender and Age - ., I Gusti Ngurah Indradhikara; ., Prof. Dr. Anak Agung Istri Ngr. Marhaeni; ., Made Hery Santosa, S.Pd, M.Pd., Ph.D. (Universitas Pendidikan Ganesha, 2017)
Penelitian ini bertujuan untuk mengidentifikasi alasan untuk menggunakan atau tidak menggunakan TIK dalam proses pembelajaran bahasa inggris. Sebanyak 54 guru dilibatkan dalam penelitian ini. Penelitian ini menggunakan metode campuran dengan desain concurrent triangulation. Penelitian ini menggunakan sebuah instrumen, yait kuesioner terbuka. Berdasarkan hasil analisis data kualitatif, baik guru laki-laki maupun perempuan, dan guru dari generasi X maupun Y sadar akan pentingnya TIK dalam proses pembelajaran bahasa inggris juga keterbatasan mereka dalam menggunakan TIK dalam mengajar. Pengembangan lebih lanjut disarankan kepada pemerintah, guru bahasa inggris, dan peneliti lainya untuk meningkatkan penggunaan TIK dalam mengajar. Kata Kunci : TIK, Gender, Umur. This study aimed to identify the reasons implementing or not implementing ICT in the process of English teaching and learning. There were 54 of English teachers employed in this research. This research integrated mix method concurrent triangulation design. There was an instrument used in this research, namely open ended questionnaire. The quantitative data showed there were differences of ICT use across gender and ages. Based on the qualitative data analysis, both male and female, and, X and Y generations of English teachers seemed to realize the importance of ICT in English teaching and learning, including their limitation in employing ICT in teaching and learning process. Further works suggested for the government, English teachers, and other researchers to improve the number of ICT integration in teaching.keyword : ICT, Gender, Ages